Modification of Poly(Vinyl Chloride) + Epoxy Systems for Improved Thermal and Aging Stability. Issue 1 (July 2016) - Bashta, Bogdana; Brostow, Witold; Granowski, Gregory; Hnatchuk, Nathalie
Summary: Functional oligomers were synthesized via a reaction of ED‐24 epoxy resin or a peroxy derivative of that resin with free peroxy and epoxy groups with adipic acid and via interaction between derivative of pyromellitic dianhydride and peroxy derivative of the same resin in the presence of benzyl triethylammonium chloride. The effects of oligomer presence, oligomer nature and amount on the crosslinking of poly(vinyl chloride) (PVC) mixtures were investigated. The thermal stability of synthesized oligomers and PVC mixtures based on them were determined, as was resistance to aging. Schematics of cross‐linking reactions of modified mixtures are proposed. Higher thermal stability and better resistance to aging have been achieved.